Treatment of intracranial aneurysms using the pipeline flex embolization device with shield technology: angiographic and safety outcomes at 1-year follow-up. (27th September 2018) - Martínez-Galdámez, Mario; Lamin, Saleh M; Lagios, Konstantinos G; Liebig, Thomas; Ciceri, Elisa F; Chapot, Rene; Stockx, Luc; Chavda, Swarupsinh; Kabbasch, Christoph; Faragò, Giuseppe; Nordmeyer, Hannes; Boulanger, Thierry; et al.
Abstract : Purpose: The Pipeline Embolization Device (PED) is a routine first-line treatment option for intracranial aneurysms (IAs). The Pipeline Flex Embolization Device with Shield Technology (Pipeline Shield) is an updated version of the PED which has been modified to include a surface phosphorylcholine biocompatible polymer. Its early technical success and safety have been reported previously. Here, we assessed the long-term safety and efficacy of the Pipeline Shield for the treatment of IAs. Materials and methods: The Pipeline Flex Embolization Device with Shield Technology (PFLEX) study was a prospective, single-arm, multicenter study for the treatment of unruptured IAs using the Pipeline Shield. The primary endpoint was a major stroke in the territory supplied by the treated artery or neurologic death at 1-year post-procedure. Angiographic outcomes were also assessed by an independent radiology laboratory at 6 months and 1 year. Results: Fifty patients (mean age, 53 years; 82% female) with 50 unruptured IAs were treated. Mean aneurysm diameter was 8.82±6.15 mm. Of the target aneurysms, 38/50 (76%) were small (<10 mm), 11/50 (22%) were large (≥10 and<25 mm), and 1/50 (2%) was giant (≥25 mm). Forty-seven (94%) were located in the internal carotid artery and three (6%) in the vertebral artery. At 1-year post-procedure, no major strokes or neurologic deaths were reported, and complete occlusion was achieved in 27/33 (81.8%). There were no instances of aneurysm recurrence or retreatment. Conclusions: Our 1-year follow-up concerning angiographic and safety outcomes corroborate previous evidence that the Pipeline Shield is a safe and effective treatment for IAs. Trial registration number: NCT02390037